Meta-analysis of minimally invasive internal thoracic artery bypass versus percutaneous revascularisation for isolated lesions of the left anterior descending artery. Issue 7594 (2nd March 2007) - Aziz, Omer; Rao, Christopher; Panesar, Sukhmeet Singh; Jones, Catherine; Morris, Stephen; Darzi, Ara; Athanasiou, Thanos
Abstract : Objective To compare outcomes between minimally invasive left internal thoracic artery bypass and percutaneous coronary artery stenting as primary interventions for isolated lesions of the left anterior descending artery. Design Meta-analysis of randomised and non-randomised comparative peer reviewed publications. Data sources Embase, Medline, Cochrane, Google Scholar, and Health Technology Assessment databases (1966-2005). Review methods Studies comparing the two procedures as the primary intervention for isolated left anterior descending artery stenosis were identified and the following extracted: study design, population characteristics, severity of coronary artery disease, cardiovascular risk factors, and outcomes of interest. Results 12 studies (1952 patients) reporting results from eight groups were included: one was a retrospective design, one prospective non-randomised, and six prospective randomised. Meta-analysis of randomised trials showed a higher rate of recurrence of angina (odds ratio 2.62, 95% confidence interval 1.32 to 5.21), incidence of major adverse coronary and cerebral events (2.86, 1.62 to 5.08), and need for repeat revascularisation (4.63, 2.52 to 8.51) with percutaneous stenting. No significant difference was found in myocardial infarction, stroke, or mortality at maximum follow-up between interventions. Conclusions Minimally invasive left internal thoracic artery bypass for isolated lesions of the left anterior descending artery resulted in fewer complications in the mid-term compared with percutaneous transluminal coronary artery stenting.